G173(P) Hidden neurodiversity in paediatric practice: Klinefelter syndrome. (24th May 2017) - Lineen, C; Khan, U; Hassan, M; Murphy, AM
Abstract : Introduction: Klinefelter syndrome has a reported incidence of 1 in 500 live male births. It is commonly diagnosed in adulthood but the majority of cases go undiagnosed. Early diagnosis and intervention can be of medical, psychological and fertility benefit. Aim: Our aim is to present four unexpected cases of Klinefelter Syndrome who presented to general paediatrics in an effort to raise awareness of this under recognised phenomenon. Methods: Clinical details and natural history of all four patients were identified from hospital records. A literature search was conducted on the optimal management of Klinefelter syndrome. Results: Case one was diagnosed at the age of 18 months with global developmental delay, plagiocephaly and absent testes. His karyotype demonstrated 49 XXXY. Case two (47 XXY, with deletions on chromosomes 14 and 19) was diagnosed at the age of 10 years. His karyotype was tested because he had an extensive family history of chromosomal deletions and his family wished to know if he had the same. He had a history of motor delay (including hypotonia since birth) and cryptorchidism. Case three (47 XXY) was diagnosed at the age of 5 years with a history of social, psychological and speech delay. He had a history of emotional problems and tantrums. Case four (47 XXY) was diagnosed at the age of 11 months, after presenting with macrocephaly and plagiocephaly, with a normal neurological exam and normal brain MRI. Conclusion: Klinefelter syndrome can present variably and subtly. Increased clinical suspicion can detect cases more frequently and earlier, providing optimal management options.